Live-cell imaging and analysis of 3D spheroids in hypoxia- and radiotherapy-related research - Claire Beckers; Lazaros Vasilikos; Lorena Moor; Martin Pruschy (Clinical and Translational Radiation Oncology)
3D spheroids are a valuable tool for investigating the interplay between hypoxia and radioresistance. However, standardized methods for visualizing normoxic and hypoxic regions within spheroids and assessing treatment responses are lacking. We developed a straightforward workflow for the analysis of spheroids based on image processing using a novel custom-written script, and flow cytometry.